Effect of Sintering Temperature on Physical Properties & hardness of CoCrMo alloys fabricated by metal injection moulding process - Ahmad Ridwan, Abdullah; Nur Aidah Nabihah, Dandang; Nur Zalikha, Khalil; W. S., Wan Harun (IOP Publishing, 2017)
Metal Injection Moulding (MIM) process is one of the Powder Metallurgy manufacturing techniques utilised to produce Cobalt Chromium Molybdenum (CoCrMo) compacts. The objective of this study is to determine physical properties and hardness of CoCrMo alloy compact sintered at three different sintering temperature at the similar soaking time. At the beginning, sample were fabricated by using Injection Moulding machine. Cobalt Chrome Molybdenum (CoCrMo) metal powder was selected for this study. A morphological study was conducted using optical microscope (OM) and micro-Vickers hardness testing. From the result obtained, it shows upward trend either on the hardness or physical properties of the samples. CoCrMo sintered compact become harder and volume of pores on surface become less due to the increase on sintering temperature. However, effect of increasing sintering temperature shows significant shrinkage of the sample, beginning losses in dimensional accuracy. It is discovered that a little change in sintering temperature gives significant impact on the microstructure, physical, mechanical of the alloy.